2005
DOI: 10.1021/jp045902r
|View full text |Cite
|
Sign up to set email alerts
|

Surface Characterization of Chromia for Chlorine/Fluorine Exchange Reactions

Abstract: The dismutation of CCl(2)F(2) was used to probe the effect of halogenation of chromia by Cl/F exchange reactions to find out the difference between the halogenated inactive and active catalysts. The heterogeneous reactions were performed in a continuous flow Ni reactor and also under simulated reaction conditions in a reactor where after the reaction X-ray photoelectron spectroscopy (XPS) and X-ray excited Auger electron spectroscopy (XAES) analyses are possible without air exposure of the catalyst, i.e., unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Also, the peak centered at 713.1 eV is not clear. From the publication of Unveren et al, it could possibly be ascribed to Fe(III) hydroxide–fluoride mix compound. The BE of Cr2p 3/2 , which peaked at 576.7 eV, is close to BE of Cr 2 O 3 (575.9–576.8 eV).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Also, the peak centered at 713.1 eV is not clear. From the publication of Unveren et al, it could possibly be ascribed to Fe(III) hydroxide–fluoride mix compound. The BE of Cr2p 3/2 , which peaked at 576.7 eV, is close to BE of Cr 2 O 3 (575.9–576.8 eV).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Moreover, Ü nveren et al [29] reported that the interaction of CCl 2 F 2 and surface Cr oxide could generate chromium oxide chloride species, which are also active in the reaction. Thus, the gradual interaction between CCl 2 F 2 and partial Cr 2 O 3 may result in the transfer of Cl element to the catalyst surface, and formed a few amorphous and more active chromium oxide chloride species, which could cause the initial induction period during the reaction.…”
Section: Influence Of Surface Aciditymentioning
confidence: 99%
“…Various fluorocarbons could be synthesized by chlorine/fluorination exchange reactions, in which Cr-based catalysts have been widely applied. These Cr-based catalysts include chromium oxides [1][2][3][4][5] and chromium-based catalysts [6][7][8][9] supported on Al 2 O 3 , AlF 3 , MgO, or MgF 2 and the deactivation of CrO x F y -AlF 3 -based catalysts in commercial processes of Cl/F exchange reaction has been investigated by Albonetti et al [10]. The performance of the Cr-based catalysts is determined by various factors such as surface area and morphologies of the Cr species.…”
Section: Introductionmentioning
confidence: 99%